RESPON PERTUMBUHAN DAN PRODUKSI TANAMAN UBI JALAR UNGU TERHADAP PEMUPUKAN NPK - Subaedah, St.; Saida, Saida (AGROTEK: Jurnal Ilmiah Ilmu Pertanian, 2025)
Sweet potatoes have great potential as an alternative food ingredient, even as a staple in some areas because of their high carbohydrate content. Various types of sweet potatoes can be cultivated, such as sweet potatoes whose tubers are white, yellow, and purple.  Sweet potatoes, whose tuber flesh is purple, contain many anthocyanins that act as antioxidants that bind free radical groups as a cancer-preventative and youth remedy.  Judging from its high nutritional content, efforts are needed to develop purple sweet potatoes which can be achieved by extensification and intensification.  Extensification efforts are faced with the use of marginal land which is characterized by low soil fertility and limited water availability.  Therefore, efforts are needed to improve soil fertility by fertilizing.This research was carried out to analyze the response to the growth and production of purple sweet potato plants with NPK fertilization. The research was carried out in the form of a field experiment in Takalar Regency.  The research lasted approximately 5 months.  The experiment was designed with a randomized block design consisting of four NPK fertilizer treatments, namely 0 kg/ha, 100 kg/ha, 200 kg/ha, and 300 kg/ha. Each treatment was repeated four times to obtain 16 experimental units.  The variables observed in this research were levels of N-total, P-total, P-available, plant length, number of tubers per plant, and weight of tubers per plant.  The results showed that NPK fertilization had a significant effect on the production of purple sweet potatoes with the best dose obtained at 300 kg/ha of NPK.